EFICIENCIA AGRONOMICA DE FONTES DE ADUBAÇÃO NITROGENADA EM TRIGO - Fontaniva, Cristiano; Oliveira, Juliana M. d.; Zambonato, Felipe; Wagner, Juliano F.; Matter, Edegar; Noronha, Uelinton; Berto, Jorge L.; Carbonera, Roberto; Quadros, Valmir J. d.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo